Perubahan Pola Pemilikan Tanah Dan Kesannya Terhadap Masyarakat Luar Bandar Di Kabupaten Blitar, Indonesia - Arisudi, Moh. Azis (2012)
Majority of the Indonesian depend on the agricultural sector. Hence, land ownership is important to their overall sustenance and returns on investment. In recent times, land per-capita of the people is decreasing. Changes in land ownership have magnitude of implications, such as from the socio-economic, socio-cultural and environmental dimensions. The objectives of this research are: first, to identify and analyze the factors that causes the occurrence of a change of ownership of land. Second, to analyze the factors that contributes to inequality in land ownership distribution. Third, to analyze the impacts of land ownership distribution to the socio-economic livelihood, socio-cultural and environmental degradation. Fourth, to review the coping strategies of the rural community who have limited of land. This research is conducted in the Blitar regency, Indonesia. The type of data used in this research is from primary and secondary data. This research uses mix method; qualitative and quantitative methods. The qualitative methods are derived from in-depth interview and focus group discussion. Meanwhile the quantitative method employs a household survey. The sampling method for the qualitative method is quota sampling, while for quantitative method is stratified random sampling, with distant between the villages to the urban centre as stratification factor. The findings of this research show that land ownership has a significant relationship with income and changing in land ownership has significant impact on the socio-economic aspects, socio-cultural and environmental degradation.